2021
DOI: 10.1016/j.sjbs.2021.03.044
|View full text |Cite
|
Sign up to set email alerts
|

Biostimulation potential of biochar for remediating the crude oil contaminated soil and plant growth

Abstract: Crude oil contamination is a serious environmental threat to soil and plants growing in it. Biochar has the potential of biostimulation for remediation of crude oil-contaminated soil. Therefore, the current research was designed to analyze the bio-stimulatory impact of biochar for remediating the crude oil contaminated soil (10%, and 15%), and growth of maize under glasshouse conditions. Biochar was produced by pyrolysis of Australian pines at 350 °C. Soil incubations were done for 20 days. The results of soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 53 publications
(43 reference statements)
0
12
0
1
Order By: Relevance
“…Its slow-release property might be the reason why plant growth was not noticed in the early weeks of planting. Saeed et al (2021) also observed an increase in fresh and dry biomass due to the incubation of biochar in crude oil-contaminated soils. Shahid et al (2017) reported an improvement in plant growth due to remediation.…”
Section: Effect Of Biochar On Growth Of Cowpea In Contaminated Soilmentioning
confidence: 73%
See 3 more Smart Citations
“…Its slow-release property might be the reason why plant growth was not noticed in the early weeks of planting. Saeed et al (2021) also observed an increase in fresh and dry biomass due to the incubation of biochar in crude oil-contaminated soils. Shahid et al (2017) reported an improvement in plant growth due to remediation.…”
Section: Effect Of Biochar On Growth Of Cowpea In Contaminated Soilmentioning
confidence: 73%
“…This is in line with the works of Ibrahim et al (2016) who reported increased TPH remediation with an increase in rate of activated carbon. Previous studies have also demonstrated the bio-stimulating potential of biochar for degradation of hydrocarbons in crude oil contaminated soil (Qin et al, 2013;Saeed et al, 2021). Galitskaya et al (2016) also reported that the addition of biochar to oil-polluted soils that were mixed and moistened resulted in an increase in hydrocarbon degradation rates compared to when mixing and moistening was used alone.…”
Section: Effect Of Biochar On Tph Degradation Efficiencymentioning
confidence: 93%
See 2 more Smart Citations
“…При внесении грибов Fusarium equiseti и Cylindrocarpon magnusianum на 10% нефтезагрязненных почвах межфазная активность гриба Fusarium equiseti, в сочетании с фиторемедиатом и биопрепаратом, почти в 1,2 и 1,5 раза превышала вариант с применением гриба Cylindrocarpon magnusianum в полном комплексе мелиорантов [8]. По данным ученых, биоуголь, как потенциальный сорбент для удаления и разложения нефти в почвах, повысил скорость очистки на 52,2% и активность фермента каталазы в 1,8 раза по сравнению с контролем [9], биоуголь усиливает микробную и ферментативную активность почвы, активность по разложению углеводородов [10]. При непосредственном использовании ферментов природные ферменты микроорганизмов используются для разложения загрязнителей окружающей среды [11].…”
unclassified